Meningkatkan Kualitas Hidup Pasien Diabetes Melitus Melalui Self Care Management - Yasmin Nur Muazizah; Yanti Cahyati; Noorgita x Noorgita Arsyi; Resa Wardeni (FORIKES, 2022)
Diabetes mellitus is a chronic disease that occurs when the pancreas does not produce enough insulin or when the body does not use insulin efficiently. Insulin is a hormone that regulates blood sugar levels. The purpose of this study was to analyze the effect of self care management on the quality of life of patients with diabetes mellitus. Self care management is dietary compliance, medication consumption compliance, monitoring blood sugar levels, physical activity/sports and foot care. This study is a systematic literature review. Articles were taken from Google Scholar from 2017 to 2020. Article searches were carried out using various search engines with the keywords “diabetes mellitus, self care, self care management, and quality of life”. Based on the results of a review of 6 articles, it is known that self care management has an effect on the quality of life of patients with diabetes mellitus. Furthermore, it is concluded that self care management is an effort that can be done to maintain the quality of life in good condition.Keywords: diabetes mellitus; self-care management; blood sugar levels; quality of life ABSTRAK Diabetes mellitus adalah penyakit kronik yang terjadi ketika pankreas tidak cukup dalam memproduksi insulin atau ketika tubuh tidak efisien menggunakan insulin itu sendiri. Insulin adalah hormon yang mengatur kadar gula darah. Tujuan penelitian ini adalah untuk menganalisis pengaruh self care management terhadap kualitas hidup pasien diabetes mellitus. Self care management adalah kepatuhan diet, kepatuhan konsumsi obat, pemantauan kadar gula darah, aktivitas fisik/olahraga dan perawatan kaki. Studi ini merupakan systematic literatur review. Artikel diambil dari Google Scholar dari tahun 2017 sampai 2020. Penelusuran artikel dilakukan dengan berbagai search engine dengan kata kunci “diabetes mellitus, self care, self care management, dan kualitas hidup”. Berdasarkan hasil review dari 6 artikel, diketahui bahwa dengan self care management berpengaruh pada kualitas hidup pasien diabetes mellitus. Selanjutnya disimpulkan bahwa self care management adalah upaya yang dapat dilakukan untuk mempertahankan kualitas hidup dalam keadaan baik.Kata kunci: diabetes mellitus; self care management; kadar gula darah; kualitas hidup